Covariance differencing‐based angle estimation method for bistatic multiple‐input–multiple‐output radar in unknown coloured noise. Issue 8 (16th August 2017) - Wen, Fangqing; Zhang, Zijing; Wang, Ke; Sheng, Guanqun
Abstract : A new angle estimation method is developed for bistatic multiple‐input–multiple‐output radar in the presence of unknown coloured noise. By utilising covariance differencing, the proposed method can eliminate influence of coloured noise effectively. Then, the angles are determined from the subspace estimate with the help of reduced‐dimension multiple signal classification (MUSIC) method. The proposed method does not incur virtual aperture loss, and it is suitable for arbitrary array manifold. Numerical simulations verify the effectiveness of the authors' method.